Efficacy of a new educational tool to improve Handrubbing technique amongst healthcare workers: a controlled, before-after study. - Lacey, Gerard (My University, 2014)
Introduction: Hand hygiene is a key component of infection control in healthcare. WHO recommends that healthcare workers perform six specific poses during each hand hygiene action. SureWash (Glanta Ltd, Dublin, Ireland) is a novel device that uses video-measurement technology and immediate feedback to teach this technique. We assessed the impact of self- directed SureWash use on healthcare worker hand hygiene technique and evaluated the device’s diagnostic capacity. Methods: A controlled before-after study: subjects in Group A were exposed to the SureWash for four weeks followed by Group B for 12 weeks. Each subject’s hand hygiene technique was assessed by blinded observers at baseline (T 0 ) and following intervention periods (T 1 and T 2 ). Primary outcome was performance of a complete hand hygiene action, requiring all six poses during an action lasting $ 20 seconds. The number of poses per hand hygiene action (maximum 6) was assessed in a post-hoc analysis. SureWash’s diagnostic capacity compared to human observers was assessed using ROC curve analysis. Results: Thirty-four and 29 healthcare workers were recruited to groups A and B, respectively. No participants performed a complete action at baseline. At T 1 , one Group A participant and no Group B participants performed a complete action. At baseline, the median number of poses performed per action was 2.0 and 1.0 in Groups A and B, respectively (p = 0.12). At T 1 , the number of poses per action was greater in Group A (post-intervention) than Group B (control): median 3.8 and 2.0, respectively (p , 0.001). In Group A, the number of poses performed twelve weeks post-intervention (median 3.0) remained higher than baseline (p , 0.001). The area under the ROC curves for the 6 poses ranged from 0.59 to 0.88. Discussion: While no impact on complete actions was demonstrated, SureWash significantly increased the number of poses per hand hygiene action and demonstrated good diagnostic capacity
PUBLISHED
Keywords: Infection control; Hand Hygiene